2023
DOI: 10.1155/2023/5996144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Coronary Artery Disease Based on Cuproptosis

Abstract: Identifying peripheral biomarkers is an important noninvasive diagnosis method for coronary artery disease (CAD) which has aroused the strong interest of researchers. Cuproptosis, a newly reported kind of programmed cell death, is closely related to mitochondrial respiration, adenosine triphosphate (ATP) production, and the TCA cycle. Currently, no studies have been published about the effects of cuproptosis-related genes (CRGs) on diagnosing CAD. To screen marker genes for CAD from CRGs, we downloaded the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…SORD is a dehydrogenase/reductase protein and plays a role in the metabolism of glucose ( 30 ). Studies have indicated SORD’s involvement as a cuproptosis-related gene in coronary artery disease ( 31 ). SLC11A2 is a key protein that aids the absorption of iron and its influence extends to breast and colon cancer progression ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…SORD is a dehydrogenase/reductase protein and plays a role in the metabolism of glucose ( 30 ). Studies have indicated SORD’s involvement as a cuproptosis-related gene in coronary artery disease ( 31 ). SLC11A2 is a key protein that aids the absorption of iron and its influence extends to breast and colon cancer progression ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cuproptosis can affect the progression of CVD. Zhang’s team found five CRGs (F5, MT4, RNF7, S100A12, and SORD) to be the potential diagnostic biomarkers for coronary artery disease (CAD) [ 85 ]. Huo et al discovered that advanced glycosylation end products (AGEs) can promote cuproptosis via ATF3/SPI1/SLC31A1 pathway and thus worsen diabetic myocardial function [ 86 ].…”
Section: Potential Role Of Cuproptosis In Non-cancer Diseasesmentioning
confidence: 99%
“…Kunutsor et al showed that a higher serum copper level increases the risk of atherosclerotic heart disease by regulating lipid metabolism, low-density lipoprotein oxidation, and inflammatory response [27]. Cuproptosis, a recently discovered copper ion-dependent programmed cell death, could thus be implicated in the development of coronary artery disease, and the genes associated with cuproptosis may serve as marker genes for coronary artery disease [28].…”
Section: Effects Of Copper and Zinc On Heart Functioningmentioning
confidence: 99%